Lipid phosphate phosphatases and lipid phosphate signalling. (26th October 2005) - Pyne, S.; Long, J.S.; Ktistakis, N.T.; Pyne, N.J.
Abstract : Mammalian LPPs (lipid phosphate phosphatases) are integral membrane proteins that belong to a superfamily of lipid phosphatases/phosphotransferases. They have broad substrate specificity in vitro, dephosphorylating PA (phosphatidic acid), S1P (sphingosine 1-phosphate), LPA (lysophosphatidic acid) etc. Their physiological role may include the attenuation of S1P- and LPA-stimulated signalling by virtue of an ecto-activity (i.e. dephosphorylation of extracellular S1P and LPA), thereby limiting the activation of LPA- and S1P-specific G-protein-coupled receptors at the cell surface. However, our recent work suggests that an intracellular action of LPP2 and LPP3 may account for the reduced agonist-stimulated p42/p44 mitogen-activated protein kinase activation of HEK-293 (human embryonic kidney 293) cells. This may involve a reduction in the basal levels of PA and S1P respectively and the presence of an early apoptotic phenotype under conditions of stress (serum deprivation). Additionally, we describe a model whereby LPP2, but not LPP3, may be functionally linked to the phospholipase D1-derived PA-dependent recruitment of sphingosine kinase 1 to the perinuclear compartment. We also consider the potential regulatory mechanisms for LPPs, which may involve oligomerization. Lastly, we highlight many aspects of the LPP biology that remain to be fully defined.